Antioxidant effects of açaí seed ( Euterpe oleracea ) in anorexia-cachexia syndrome induced by Walker-256 tumor - Vitor Hugo Nunes do Nascimento; Carla dos Santos Lima; Jorge Tadeu Campos Paixão; Jofre Jacob da Silva Freitas; Katia Simone Kietzer (Acta Cirúrgica Brasileira, 2016)
ABSTRACT PURPOSE: To assess antioxidant effects of açaí seed extract on anorexia-cachexia induced by Walker-256 tumor. METHODS: A population of 20 lab rats were distributed into four groups (n=5): Control Group (CG), which only received tumor inoculation. Experimental Group-100 (EG-100), with animals submitted to tumor inoculation and treated with seed extract in a 100 mg / ml concentration through gavage. Experimental Group-200 (EG-200), with animals submitted to tumor inoculation and treated with seed extract in a 200 mg / ml concentration. Placebo Group (GP), which received tumor inoculation and ethanol-water solution. We analyzed proteolysis, lipid peroxidation, tumor diameter and weight. RESULTS: Lipid peroxidation was representative only in the cerebral cortex, where there was more oxidative stress in rats treated with the extract (p = 0.0276). For proteolysis, there was less muscle damage in untreated rats (p = 0.0312). Only tumor diameter in treated rats was significantly lower (p = 0.0200) compared to untreated ones. CONCLUSIONS: The açaí seed extract showed no beneficial effect on the general framework of the cachectic syndrome in lab rats. However, some anticarcinogenic effects were observed in the tumor diameter and weight.